1989
DOI: 10.3181/00379727-191-42899
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Effects of 4-Chlorophenol in Rats: Comparison to Clofibrate

Abstract: 4-Chlorophenol (4-CP) is an identified trace contaminant in commercial clofibrate ipreparations and the pharmacologic effects of 4-CP have not yet been widely establlished. We have examined the dose-dependent effects of oral 4-CP and clofibrate adminlistration on selected hepatic parameters and on serum glucose, cholesterol, and triglyckride concentrations in male rats. 4-CP treatment (0.00125-0.08 mmol/kg, twice a day) of rats for 2 weeks increased hepatic microsomal protein (20-30%) and cytochrome P-450 (20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, after 13 weeks of exposure, the severity of hypertrophy was minimal in the 10 mg/kg/day rats, and the incidence was not statistically significantly different compared to the control rats. Hepatocyte hypertrophy is typically observed with enzyme induction; although Phornchirasilp et al [22] observed significant increases in microsomal protein and cytochrome P450 levels in Sprague-Dawley rats dosed with 4-chlorophenol, studies reporting TCP-induction of liver metabolizing enzymes were not found suggesting that other pathways may be involved in the hypertrophy response. The observed hepatocyte vacuolation in conjunction with hypertrophy (Table 5) may indicate perturbation of lipid metabolism, a common sequel to hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 13 weeks of exposure, the severity of hypertrophy was minimal in the 10 mg/kg/day rats, and the incidence was not statistically significantly different compared to the control rats. Hepatocyte hypertrophy is typically observed with enzyme induction; although Phornchirasilp et al [22] observed significant increases in microsomal protein and cytochrome P450 levels in Sprague-Dawley rats dosed with 4-chlorophenol, studies reporting TCP-induction of liver metabolizing enzymes were not found suggesting that other pathways may be involved in the hypertrophy response. The observed hepatocyte vacuolation in conjunction with hypertrophy (Table 5) may indicate perturbation of lipid metabolism, a common sequel to hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 4-chlorophenol (4-CP) is highly toxic to living organisms owing to its teratogenic, carcinogenic, and mutagenic characteristics as well as its persistence in the aquatic environments. 6 10 Moreover, the environmental and bio-degradation of 4-CP is difficult owing to its low water solubility and vapor pressure characteristics. 11 The US Environmental Protection Agency 12 and the European Union 13 have labeled 4-CP as a “priority pollutant”; that is, its presence in aquatic environments requires constant monitoring and that a concentration of 0.5 mg/L is the upper permissible limit of this compound in public water supply.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroaromatic compounds have numerous industrial applications, including petroleum refining and the production of pesticides, paints, plastics, resins, textiles, iron, solvents, pharmaceuticals, and wood-preserving chemicals. The former are released into the environment as byproducts of the latter. Among them, 4-chlorophenol (4-CP) is highly toxic to living organisms owing to its teratogenic, carcinogenic, and mutagenic characteristics as well as its persistence in the aquatic environments. Moreover, the environmental and bio-degradation of 4-CP is difficult owing to its low water solubility and vapor pressure characteristics . The US Environmental Protection Agency and the European Union have labeled 4-CP as a “priority pollutant”; that is, its presence in aquatic environments requires constant monitoring and that a concentration of 0.5 mg/L is the upper permissible limit of this compound in public water supply .…”
Section: Introductionmentioning
confidence: 99%